Electrodes, methods of making and using the same
Patent Information
- Application Number
- CN202311766064.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-20
AI Technical Summary
[0003]在这些应用领域中,常用的还是次氯酸钠型的钛电极处理装置,需要借助水中的氯离子或者需要额外加氯化钠才能起到好的杀菌效果,而且借助氯离子消毒的方式会导致其反应完后依旧长期残留其中造成污染,另外对氯的依赖性也导致该电极在很多领域无法使用
[0032]本发明第三方面提供了一种电化学装置,包括至少一个上述电极。
Smart Images

Figure CN117737779B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical technology, and more specifically, to an electrode, its preparation method, and its application. Background Technology
[0002] Ozone is a "clean disinfectant" that has a significant inactivation effect on almost all bacteria, viruses, fungi, protozoa, and oocysts. Furthermore, ozone can oxidize various odorous inorganic or organic substances, removing their odor. It can also decolorize wastewater, removing substances such as phenols, cyanides, and inorganic metal ions. Its applications are becoming increasingly widespread in advanced wastewater oxidation treatment, deep drinking water purification, environmental protection, food processing, medical care, and fruit and vegetable preservation.
[0003] In these application areas, sodium hypochlorite-type titanium electrode treatment devices are commonly used. They require the use of chloride ions in the water or the addition of sodium chloride to achieve a good sterilization effect. Moreover, the use of chloride ions for disinfection can lead to long-term residues after the reaction, causing pollution. In addition, the dependence on chlorine also makes this electrode unusable in many fields.
[0004] Some related technologies also utilize ozone to enhance sterilization effects, but the quality of these electrode products is often not guaranteed, and irreversible coating peeling can occur during use, resulting in a short service life. Summary of the Invention
[0005] To address the aforementioned problems, the main objective of this invention is to provide an electrode, its preparation method, and its applications. This method features a simple production process, requires no special storage of raw materials, significantly reduces electrode manufacturing time, saves labor costs, and produces electrodes with uniform quality control, stable and excellent performance, and a longer service life.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows:
[0007] The first aspect of the present invention provides a method for preparing an electrode, comprising:
[0008] The mixed slurry is applied to the surface of a titanium substrate and then heat-treated to obtain the electrode;
[0009] The mixed slurry includes catalyst powder and titanium salt;
[0010] The catalyst powder is an oxide comprising tin, antimony, and doped metal elements;
[0011] The electrode includes the titanium matrix and a composite oxide formed by the catalyst and titanium oxide coated on the surface of the titanium matrix.
[0012] According to an embodiment of the present invention, the doping metal element is at least one selected from platinum, tantalum, palladium, iridium, or nickel.
[0013] According to an embodiment of the present invention, the titanium salt is at least one of tetrabutyl titanate or titanium trichloride.
[0014] According to an embodiment of the present invention, the molar ratio of tin, antimony and doped metal elements is (8-15):(1-2):(0.1-0.5).
[0015] According to an embodiment of the present invention, the amount of titanium salt added is 0.5% to 10% of the mass of the catalyst powder.
[0016] According to an embodiment of the present invention, the mixed slurry further includes carbon-based materials.
[0017] According to embodiments of the present invention, the carbon-based material includes at least one of graphite, graphene, biochar, carbon spheres, carbon fibers, or carbon nanotubes.
[0018] According to an embodiment of the present invention, the amount of carbon-based material added is 0.5% to 5% of the mass of the catalyst powder.
[0019] According to an embodiment of the present invention, the method for preparing the catalyst powder includes:
[0020] Tin salt, antimony salt, and doped metal salt are added to an alcohol solvent to obtain a mixed solution;
[0021] The mixture was reacted at 60–180°C for 0.5–5 h, and an alkaline substance was added during the reaction to obtain the precursor.
[0022] The precursor is dried, ground, and then sintered at 500–800°C for 2–5 hours to obtain the catalyst powder.
[0023] According to an embodiment of the present invention, the alkaline substance is at least one of ammonia, ammonia water, or sodium hydroxide.
[0024] According to an embodiment of the present invention, when the alkaline substance is at least one of ammonia gas or ammonia water, the mixture is reacted at 60–180°C for 0.5–5 hours, and an alkaline substance is added during the reaction to obtain a precursor comprising:
[0025] The mixture is reacted at 60–180°C for 0.5–5 h, with ammonia gas or ammonia water continuously introduced during the reaction; the supernatant after the reaction is taken, ammonia water or sodium hydroxide is added, and then solid-liquid separation is performed to obtain the precursor.
[0026] According to an embodiment of the present invention, when the alkaline substance is sodium hydroxide, the mixture is reacted at 60–180°C for 0.5–5 hours, and an alkaline substance is added during the reaction to obtain a precursor comprising:
[0027] The mixture is reacted at 60–180°C for 0.5–5 h, and sodium hydroxide is added during the reaction. The precipitate after the reaction is collected to obtain the precursor.
[0028] According to an embodiment of the present invention, the step of applying the mixed slurry to the surface of the titanium substrate and then performing heat treatment includes:
[0029] The electrode is obtained by repeating the cycle of application, drying, application, drying and sintering 2 to 5 times, with the last sintering time being 1 to 2 hours.
[0030] The application involves applying the mixed slurry onto the titanium substrate, the drying involves drying at 100–120°C for 10–20 min, and the sintering involves sintering at 500–700°C for 10–20 min.
[0031] A second aspect of the present invention provides an electrode, which is prepared by the above-described electrode preparation method.
[0032] A third aspect of the present invention provides an electrochemical device comprising at least one of the electrodes described above.
[0033] The fourth aspect of the present invention provides the application of the above-mentioned electrode or the above-mentioned electrochemical device in the fields of wastewater treatment, drinking water purification, environmental protection, food processing, medical care or fruit and vegetable preservation, especially in electrochemical sterilization.
[0034] According to an embodiment of the present invention, an electrode comprising a titanium matrix and a composite oxide coated on the surface of a titanium matrix is obtained by applying a mixed slurry including catalyst powder and titanium salt to the surface of a titanium matrix and then performing heat treatment. The composite oxide is formed by an oxide catalyst including tin, antimony and doped metal elements and titanium oxide. The titanium oxide forms a transition layer between the catalyst and the titanium matrix, which increases the stability of the electrode and further improves the sterilization effect.
[0035] According to embodiments of the present invention, the production process of this method is simple, and the raw materials do not require special storage. It can significantly reduce electrode manufacturing time, save labor costs, and produce electrodes with uniform quality control, stable and excellent performance, and longer service life.
[0036] According to an embodiment of the present invention, the electrode prepared by the method provided by the present invention can generate ozone through electrolysis of water during the electrochemical reaction process to improve the sterilization effect.
[0037] According to embodiments of the present invention, the electrodes prepared by the method provided by the present invention can be well applied in wastewater treatment, drinking water purification, environmental protection, food processing, medical care, and fruit and vegetable preservation. They exhibit particularly excellent performance in electrochemical sterilization. Attached Figure Description
[0038] The above and other objects, features and advantages of the present invention will become more apparent from the following description of embodiments of the invention with reference to the accompanying drawings, in which:
[0039] Figure 1 Here is a scanning electron microscope image of the catalyst powder prepared in Example 3 of this invention;
[0040] Figure 2 This is a scanning electron microscope image of the electrode prepared in Example 3 of the present invention. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0042] Research revealed that the quality of electrode products in existing technologies is often unreliable, with irreversible coating peeling occurring during use and resulting in a short service life. In developing this invention, it was discovered that high-performance electrodes can be prepared by applying a mixed slurry comprising catalyst powder and titanium salt to the surface of a titanium substrate followed by heat treatment.
[0043] Specifically, according to embodiments of the present invention, the present invention provides a method for preparing an electrode, comprising:
[0044] The mixed slurry is applied to the surface of a titanium substrate and then heat-treated to obtain the electrode;
[0045] The mixed slurry includes catalyst powder and titanium salt;
[0046] The catalyst powder is an oxide containing tin, antimony, and doped metal elements;
[0047] The electrode comprises a titanium matrix and a composite oxide formed by a catalyst and titanium oxide coated on the surface of the titanium matrix.
[0048] According to an embodiment of the present invention, an electrode comprising a titanium matrix and a composite oxide coated on the surface of a titanium matrix is obtained by applying a mixed slurry including catalyst powder and titanium salt to the surface of a titanium matrix and then performing heat treatment. The composite oxide is formed by an oxide catalyst including tin, antimony and doped metal elements and titanium oxide. The titanium oxide forms a transition layer between the catalyst and the titanium matrix, which increases the stability of the electrode and further improves the electrode performance.
[0049] According to an embodiment of the present invention, the molar ratio of tin, antimony and doped metal elements is (8-15):(1-2):(0.1-0.5).
[0050] According to an embodiment of the present invention, the molar ratio of tin, antimony and doped metal is preferably (9-12):(1):(0.2-0.4), and more preferably 10:1:0.3.
[0051] According to embodiments of the present invention, by limiting the molar ratio of tin, antimony, and doped metal elements, the catalytic effect of the catalyst and its interfacial properties with titanium oxide can be further improved, thereby enhancing the stability and sterilization effect of the electrode.
[0052] According to embodiments of the present invention, the doping metal element is at least one selected from platinum, tantalum, palladium, iridium, or nickel.
[0053] According to an embodiment of the present invention, the catalyst powder comprises at least one of platinum, tantalum, palladium, iridium or nickel, tin and antimony. After heat treatment, the catalyst powder and titanium salt exhibit good interfacial properties, which increases the stability of the electrode.
[0054] According to embodiments of the present invention, a binder may also be added to the mixed slurry, the binder being at least one of polyethylene glycol, Nafion, or PVDF.
[0055] According to an embodiment of the present invention, the amount of binder added is 0.1% to 2% of the mass of the catalyst powder.
[0056] According to embodiments of the present invention, preferred binders and their addition ratios can keep the viscosity of the mixed slurry within a suitable range, allowing the mixed slurry to be smoothly applied to the surface of the titanium substrate.
[0057] According to embodiments of the present invention, the titanium salt is at least one of tetrabutyl titanate or titanium trichloride.
[0058] According to an embodiment of the present invention, the amount of titanium salt added is 0.5% to 10% of the mass of the catalyst powder.
[0059] According to embodiments of the present invention, the preferred titanium salt and its addition amount, after heat treatment, can form a high-performance interface layer between the catalyst and the titanium matrix, further improving the stability and performance of the electrode.
[0060] According to an embodiment of the present invention, the mixed slurry also includes carbon-based materials.
[0061] According to embodiments of the present invention, the carbon-based material includes at least one of graphite, graphene, biochar, carbon spheres, carbon fibers, or carbon nanotubes.
[0062] According to an embodiment of the present invention, the amount of carbon-based material added is 0.5% to 5% of the mass of the catalyst powder.
[0063] According to an embodiment of the present invention, adding carbon-based materials to the mixed slurry and removing them through a sintering process can enable the final catalyst to form a microporous structure, thereby further improving the catalytic effect of the catalyst.
[0064] According to an embodiment of the present invention, the method for preparing catalyst powder includes:
[0065] Tin salt, antimony salt, and doped metal salt are added to an alcohol solvent to obtain a mixed solution;
[0066] The mixture was reacted at 60–180°C for 0.5–5 h, and an alkaline substance was added during the reaction to obtain the precursor.
[0067] The precursor is dried, ground, and then sintered at 500–800℃ for 2–5 hours to obtain catalyst powder.
[0068] According to embodiments of the present invention, the catalyst powder prepared by this method has uniform morphology and excellent and stable performance.
[0069] According to embodiments of the present invention, the alcohol solvent used in the reaction process is at least one of isopropanol or n-butanol. It should be noted that other alcohol solvents that facilitate the reaction can also be used in the present invention.
[0070] According to embodiments of the present invention, the alkaline substance is at least one of ammonia gas, ammonia water, or sodium hydroxide.
[0071] According to an embodiment of the present invention, when the alkaline substance is at least one of ammonia gas or ammonia water, the mixture is reacted at 60–180°C for 0.5–5 h, and an alkaline substance is added during the reaction to obtain a precursor comprising:
[0072] The mixture is reacted at 60–180°C for 0.5–5 h, with ammonia gas or ammonia water continuously introduced during the reaction. The supernatant after the reaction is taken, ammonia water or sodium hydroxide is added, and then solid-liquid separation is performed to obtain the precursor.
[0073] According to an embodiment of the present invention, by continuously introducing ammonia gas into the reaction, the reaction can be made milder, the generated precursor substance exists in the supernatant, and the precursor precipitate is obtained by adding alkaline substances, the generated precursor is more uniform, and the catalyst powder formed after sintering has better morphological uniformity, excellent performance and stability.
[0074] According to an embodiment of the present invention, when the alkaline substance is sodium hydroxide, the mixture is reacted at 60–180°C for 0.5–5 hours, and an alkaline substance is added during the reaction to obtain a precursor comprising:
[0075] The mixture was reacted at 60–180 °C for 0.5–5 h, with sodium hydroxide added during the reaction; the precipitate after the reaction was collected to obtain the precursor.
[0076] According to an embodiment of the present invention, the preparation method is simplified by adding sodium hydroxide during the reaction process so that the generated precursor exists in the precipitate.
[0077] According to an embodiment of the present invention, applying the mixed slurry to the surface of a titanium substrate followed by heat treatment includes:
[0078] The electrode is obtained by repeating the cycle of application, drying, application, drying and sintering 2 to 5 times, with the last sintering time being 1 to 2 hours.
[0079] The application involves applying the mixed slurry onto the titanium substrate, the drying involves drying at 100–120°C for 10–20 min, and the sintering involves sintering at 500–700°C for 10–20 min.
[0080] According to embodiments of the present invention, by performing multiple cycles of application, drying, application, drying and sintering, the mixed slurry can be better coated on the surface of the titanium substrate and the production time can be shortened; increasing the time of the final sintering can make the performance of the finally prepared electrode more stable.
[0081] According to embodiments of the present invention, the mixed slurry can be applied to the surface of a titanium substrate by spraying, brushing, dipping, or flow coating. Other conceivable application methods are also feasible, such as printing methods.
[0082] According to an embodiment of the present invention, an electrode is provided, which is prepared by the electrode preparation method described above.
[0083] According to an embodiment of the present invention, an electrochemical device is provided, comprising at least one of the electrodes described above.
[0084] According to embodiments of the present invention, the above-described electrode or electrochemical device is provided for applications in wastewater treatment, drinking water purification, environmental protection, food processing, medical care, or fruit and vegetable preservation, especially in electrochemical sterilization.
[0085] According to embodiments of the present invention, this method features a simple production process, requires no special storage of raw materials, significantly reduces electrode manufacturing time, saves labor costs, and produces electrodes with uniform quality control, stable and excellent performance, and a longer service life. Electrodes prepared using the method provided by this invention can be well applied in wastewater treatment, drinking water purification, environmental protection, food processing, medical care, and fruit and vegetable preservation. They exhibit particularly excellent performance in electrochemical sterilization.
[0086] The following description is based on specific embodiments.
[0087] Example 1
[0088] This embodiment provides a method for preparing an electrode, including:
[0089] I. Preparation of catalyst powder:
[0090] Step 101: Weigh tin tetrachloride, antimony trichloride, and chloroplatinic acid and dissolve them in isopropanol to obtain a mixed solution, wherein the concentration of tin tetrachloride in the mixed solution is 1 mol / L, the concentration of antimony trichloride is 0.1 mol / L, and the concentration of chloroplatinic acid is 0.03 mol / L.
[0091] Step 102: Place the above mixture in an 80℃ oil bath and heat under reflux for 1.0 h, while continuously introducing ammonia gas during the reaction to promote the reaction at a flow rate of 0.2 L / min, to obtain a suspension.
[0092] Step 103: Centrifuge the above suspension to remove the precipitate and obtain a clear solution.
[0093] Step 104: Mix the above clear solution, an appropriate amount of distilled water and polyethylene glycol evenly, slowly add 1 mol / L ammonia water to adjust the pH value to control the formation of precipitate, let stand for 2 hours, wash with water, filter and separate, dry and grind, and then heat the powder at 600℃ for 3.0 hours to obtain catalyst powder.
[0094] II. Preparation of the mixed slurry:
[0095] Step 201: Disperse 2.5g of the sintered catalyst powder in 30mL of ethanol solution, and then place it in a ball mill and ball mill for 1.5h to obtain a suspension, wherein the mass ratio of agate beads to powder is 5:1.
[0096] Step 202: Add a certain amount of ethanol solution to the above suspension so that the mass ratio of catalyst powder in the mixture is 10%. Add tetrabutyl titanate solution and hydrochloric acid so that the tetrabutyl titanate is 3% of the mass of catalyst powder. Disperse evenly to obtain a mixed slurry.
[0097] III. Electrode Preparation:
[0098] Step 300: The above mixed slurry is evenly brushed onto the pretreated titanium mesh, and the brushing-drying-brushing-drying-sintering steps are repeated 5 times. The drying temperature is 120℃ and the drying time is 10min. The sintering temperature is 550℃ and the sintering time is 15min. The last sintering time is 2h to obtain the electrode.
[0099] The prepared electrode sheet was used as the anode, and a titanium mesh of the same size was used as the cathode. The electrolysis module was assembled in a "cathode-anode-cathode" configuration. Using a Luheng LH-D01 ozone detector, under a constant voltage of 12V, 800ml of tap water was electrolyzed for 3 minutes, and a water sample was taken for testing. The ozone concentration was 1.86mg / L. Further sterilization efficacy was tested. According to the Ministry of Health's 2002 edition of the "Disinfection Technical Specifications" (2.1.4.1), the electrolysis module was placed in 800ml of bacterial solution and supplied with DC 12V for 3 minutes. Water samples were then taken for testing, and the sterilization efficacy against Escherichia coli, Candida albicans, and Staphylococcus aureus was tested. The sterilization efficacy for all three bacteria reached 99.99%.
[0100] Example 2
[0101] This embodiment provides a method for preparing an electrode, including:
[0102] I. Preparation of catalyst powder:
[0103] Step 101: Weigh out tin tetrachloride, antimony trichloride, and tantalum pentachloride n-butanol solution and dissolve them in isopropanol to obtain a mixed solution, wherein the concentration of tin tetrachloride in the mixed solution is 1 mol / L, the concentration of antimony trichloride is 0.1 mol / L, and the concentration of tantalum pentachloride is 0.02 mol / L.
[0104] Step 102: Place the above mixture in an 85°C oil bath and heat under reflux for 1.0 h, while continuously introducing ammonia gas during the reaction to promote the reaction at a flow rate of 0.2 L / min, to obtain a suspension.
[0105] Step 103: Centrifuge the above suspension to remove the precipitate and obtain a clear solution.
[0106] Step 104: Mix the above clear solution, an appropriate amount of distilled water and polyethylene glycol evenly, slowly add 0.5 mol / L ammonia water to adjust the pH value to control the formation of precipitate, let stand for 3 hours, wash with water, filter and separate, dry and grind, and then heat the powder at 550℃ for 2.0 hours to obtain catalyst powder.
[0107] II. Preparation of the mixed slurry:
[0108] Step 201: Disperse 2.5g of the sintered catalyst powder and 0.075g of short carboxylated multi-walled carbon nanotubes in 30mL of ethanol solution, and then place them in a ball mill for 1.5h to obtain a suspension, wherein the mass ratio of agate beads to powder is 3:1.
[0109] Step 202: Add a certain amount of ethanol solution to the above suspension so that the mass ratio of catalyst powder in the mixture is 10%. Add titanium trichloride hydrochloric acid solution so that titanium trichloride is 0.5% of the mass of catalyst powder. Disperse evenly to obtain a mixed slurry.
[0110] III. Electrode Preparation:
[0111] Step 300: The above mixed slurry is evenly brushed onto the pretreated titanium mesh, and the brushing-drying-brushing-drying-sintering steps are repeated 5 times. The drying temperature is 100℃ and the drying time is 10min. The sintering temperature is 550℃ and the sintering time is 10min. The last sintering time is 2h to obtain the electrode.
[0112] The prepared electrode sheet was used as the anode, and a titanium mesh of the same size was used as the cathode. The electrolysis module was assembled in a "cathode-anode-cathode" configuration. Using a Luheng LH-D01 ozone detector at a constant voltage of 12V, 800ml of tap water was electrolyzed for 3 minutes, and a water sample was taken for testing. The ozone concentration was 1.93mg / L. Further testing of the sterilization effect was conducted by placing the electrolysis module in 1000ml of tap water and electrolyzing for 1 minute. 1ml of the electrolyte was then added to a solution with a concentration of 9*10... 7 The bacterial suspension of CFU / mol was shaken evenly, and the sample was dropped onto a bacterial counting plate. After incubation in a constant temperature incubator for 24 hours, the bactericidal and bacteriostatic effects were observed. The control group was treated with 1 ml of sterile water, and the rest remained unchanged. The bacterial counting plate of the experimental group was clean and free of E. coli, while the counting plate of the control group had a large number of visible colonies.
[0113] Example 3
[0114] This embodiment provides a method for preparing an electrode, including:
[0115] I. Preparation of catalyst powder:
[0116] Step 101: Weigh tin tetrachloride, antimony trichloride, and palladium chloride and dissolve them in isopropanol to obtain a mixed solution, wherein the concentration of tin tetrachloride in the mixed solution is 1 mol / L, the concentration of antimony trichloride is 0.1 mol / L, and the concentration of palladium chloride is 0.03 mol / L.
[0117] Step 102: Place the above mixture in a 90℃ oil bath and heat under reflux for 1.0 h, while continuously introducing ammonia gas during the reaction to promote the reaction at a flow rate of 0.2 L / min, to obtain a suspension.
[0118] Step 103: Centrifuge the above suspension to remove the precipitate and obtain a clear solution.
[0119] Step 104: Mix the above clarified solution, an appropriate amount of distilled water, and polyethylene glycol evenly. Adjust the pH value by slowly adding 1 mol / L ammonia water to control precipitate formation. Let stand for 3 hours, wash with water, filter, separate, dry, and grind. After grinding, heat the powder at 550℃ for 1.5 hours to obtain catalyst powder. The obtained catalyst powder was examined by scanning electron microscopy (SEM). See the SEM images for details. Figure 1 ,Depend on Figure 1 It can be seen that the prepared catalyst powder has a uniform morphology.
[0120] II. Preparation of the mixed slurry:
[0121] Step 201: Disperse 2.5g of the sintered catalyst powder in 30mL of ethanol solution, and then place it in a ball mill and ball mill for 1.0h to obtain a suspension, wherein the mass ratio of agate beads to powder is 10:1.
[0122] Step 202: Add a certain amount of ethanol solution to the above suspension so that the mass ratio of catalyst powder in the mixture is 10%. Add titanium trichloride hydrochloric acid solution so that titanium trichloride is 10% of the mass of catalyst powder. Disperse evenly to obtain a mixed slurry.
[0123] III. Electrode Preparation:
[0124] Step 300: The above-mentioned mixed slurry is uniformly brushed onto the pre-treated titanium mesh. The process of brushing-drying-brushing-drying-sintering is repeated 5 times. The drying temperature is 100℃, and the drying time is 10 min. The sintering temperature is 520℃, and the sintering time is 10 min, with the final sintering time being 1.5 h. The resulting electrode is then examined using a scanning electron microscope (SEM). See the SEM images for details. Figure 2 ,Depend on Figure 2 It can be seen that the prepared electrode surface is coated with a uniformly distributed catalytic material.
[0125] The prepared electrode sheet was used as the anode, and a titanium mesh of the same size was used as the cathode. The electrolysis module was assembled in a "cathode-anode-cathode" configuration. Using a Luheng LH-D01 ozone detector at a constant voltage of 12V, 800ml of tap water was electrolyzed for 3 minutes, and a water sample was taken for testing. The ozone concentration was 2.16mg / L. To further test the deodorization effect, the electrolysis module was placed in 1000ml of tap water and electrolyzed for 1 minute. 100ml of the electrolyte was then added to 100ml of odorous domestic sewage. After shaking for a short time, the odor was largely eliminated.
[0126] Example 4
[0127] This embodiment provides a method for preparing an electrode, including:
[0128] I. Preparation of catalyst powder:
[0129] Step 101: Weigh stannous chloride, antimony trichloride, and chloroiridic acid and dissolve them in isopropanol. Then add tantalum pentachloride n-butanol solution to obtain a mixed solution. The concentration of stannous chloride in the mixed solution is 1 mol / L, the concentration of antimony trichloride is 0.1 mol / L, the concentration of chloroiridic acid is 0.02 mol / L, and the concentration of tantalum pentachloride is 0.008 mol / L.
[0130] Step 102: Place the above mixture in a 90℃ oil bath and heat under reflux for 1.0 h, while continuously introducing ammonia gas during the reaction to promote the reaction at a flow rate of 0.2 L / min, to obtain a suspension.
[0131] Step 103: Centrifuge the above suspension to remove the precipitate and obtain a clear solution.
[0132] Step 104: Mix the above clear solution, an appropriate amount of distilled water and polyethylene glycol evenly, slowly add 0.5 mol / L ammonia water to adjust the pH value to control the formation of precipitate, let stand for 3 hours, wash with water, filter and separate, dry and grind, and then heat the powder at 500℃ for 2.0 hours to obtain catalyst powder.
[0133] II. Preparation of the mixed slurry:
[0134] Step 201: Disperse 2g of the sintered catalyst powder in 30mL of ethanol solution, and then place it in a ball mill and ball mill for 1.0h to obtain a suspension, wherein the mass ratio of agate beads to powder is 6:1.
[0135] Step 202: Add a certain amount of ethanol solution to the above suspension so that the mass ratio of catalyst powder in the mixture is 10%. Add titanium trichloride hydrochloric acid solution so that titanium trichloride is 3% of the mass of catalyst powder. Disperse evenly to obtain a mixed slurry.
[0136] III. Electrode Preparation:
[0137] Step 300: The above mixed slurry is evenly brushed onto the pretreated titanium mesh, and the brushing-drying-brushing-drying-sintering steps are repeated 5 times. The drying temperature is 110℃ and the drying time is 15min. The sintering temperature is 550℃ and the sintering time is 10min. The last sintering time is 2h to obtain the electrode.
[0138] Example 5
[0139] This embodiment provides a method for preparing an electrode, including:
[0140] I. Preparation of catalyst powder:
[0141] Step 101: Weigh stannous chloride, antimony trichloride, chloroplatinic acid, and nickel chloride and dissolve them in isopropanol to obtain a mixed solution, wherein the concentration of stannous chloride in the mixed solution is 1 mol / L, the concentration of antimony trichloride is 0.2 mol / L, the concentration of chloroplatinic acid is 0.025 mol / L, and the concentration of nickel chloride is 0.005 mol / L.
[0142] Step 102: Place the above mixture in an oil bath at 160°C and heat until dissolved. Add sodium hydroxide and heat under reflux for 1.5 hours to obtain a suspension.
[0143] Step 103: Cool the above suspension to room temperature and then slowly add an appropriate amount of purified water, then centrifuge to obtain the precipitate.
[0144] Step 104: After washing, filtering and separating the above precipitate with water, drying and grinding, the powder is heated at 600℃ for 2.0h to obtain catalyst powder.
[0145] II. Preparation of the mixed slurry:
[0146] Step 201: Disperse 3g of the sintered catalyst powder in 30mL of ethanol solution, and then place it in a ball mill and ball mill for 1.0h to obtain a suspension, wherein the mass ratio of agate beads to powder is 3:1.
[0147] Step 202: Add a certain amount of ethanol solution to the above suspension so that the mass ratio of catalyst powder in the mixture is 10%. Add titanium trichloride hydrochloric acid solution so that titanium trichloride is 3% of the mass of catalyst powder. Then add 0.01g of polyethylene glycol and disperse evenly to obtain a mixed slurry.
[0148] III. Electrode Preparation:
[0149] Step 300: The above mixed slurry is evenly brushed onto the pretreated titanium mesh, and the brushing-drying-brushing-drying-sintering steps are repeated 5 times. The drying temperature is 110℃ and the drying time is 15min. The sintering temperature is 550℃ and the sintering time is 10min. The last sintering time is 2h to obtain the electrode.
[0150] Comparative Example 1
[0151] The electrode preparation method provided in this comparative example is the same as in Example 1, except that tetrabutyl titanate is not added in step 202.
[0152] The prepared electrode sheet was used as the anode, and a titanium mesh of the same size was used as the cathode. The electrolysis module was assembled in a "cathode-anode-cathode" configuration. Using a Luheng LH-D01 ozone detector, under a constant voltage of 12V, 800ml of tap water was electrolyzed for 3 minutes, and a water sample was taken for testing. The ozone concentration was 1.21mg / L. Further sterilization efficacy was tested. According to the Ministry of Health's 2002 edition of the "Disinfection Technical Specifications" (2.1.4.1), the module was placed in 800ml of bacterial solution and supplied with DC 12V for 3 minutes. Water samples were then taken for testing, and the sterilization efficacy against Escherichia coli, Candida albicans, and Staphylococcus aureus was examined. The sterilization efficacy in all three bacteria reached 95%.
[0153] Comparative Example 2
[0154] The electrode preparation method provided in this comparative example refers to Example 1, except that in step 101: tin tetrachloride, palladium chloride, and chloroplatinic acid are weighed and dissolved in isopropanol to obtain a mixed solution, wherein the concentration of tin tetrachloride in the mixed solution is 1 mol / L, the concentration of palladium chloride is 0.1 mol / L, and the concentration of chloroplatinic acid is 0.03 mol / L.
[0155] The prepared electrode sheet was used as the anode, and a titanium mesh of the same size was used as the cathode. The electrolysis module was assembled in a "cathode-anode-cathode" configuration. Using a Luheng LH-D01 ozone detector, under a constant voltage of 12V, 800ml of tap water was electrolyzed for 3 minutes, and a water sample was taken for testing. The ozone concentration was 0.86mg / L. Further sterilization efficacy was tested. According to the Ministry of Health's 2002 edition of the "Disinfection Technical Specifications" (2.1.4.1), the module was placed in 800ml of bacterial solution and supplied with DC 12V for 3 minutes. Water samples were then taken for testing, and the sterilization efficacy against Escherichia coli, Candida albicans, and Staphylococcus aureus was examined. The sterilization efficacy in all three bacteria reached 80%.
[0156] Experimental Example 1
[0157] Using the electrode sheet prepared in Example 1 as the anode and a titanium mesh of the same size as the cathode, an electrolysis module was assembled in a "cathode-anode-cathode" configuration. According to the Ministry of Health's 2002 edition of the "Disinfection Technical Specifications" (2.1.4.1), the module was placed in 800ml of bacterial solution and supplied with DC 12V power. After 3 minutes, the solution was replaced with a new 800ml of bacterial solution. This process was repeated 60 times. Water samples were taken for testing to evaluate the bactericidal effect against three bacteria: Escherichia coli, Candida albicans, and Staphylococcus aureus. The bactericidal effect reached 99.9% in all cases.
[0158] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an electrode, comprising: The mixed slurry is applied to the surface of a titanium substrate and then heat-treated to obtain the electrode; The mixed slurry includes catalyst powder and titanium salt; The catalyst powder is an oxide comprising tin, antimony, and doped metal elements; The doped metal element is at least one of platinum, tantalum, palladium, and iridium; The molar ratio of tin, antimony, and doped metal elements is (8~15):(1~2):(0.1~0.5). The amount of titanium salt added is 0.5% to 10% of the mass of the catalyst powder; The electrode includes the titanium matrix and a composite oxide formed by the catalyst and titanium oxide coated on the surface of the titanium matrix.
2. The preparation method according to claim 1, wherein, The titanium salt is at least one of tetrabutyl titanate or titanium trichloride.
3. The preparation method according to claim 1, wherein, The mixed slurry also includes carbon-based materials; The carbon-based material includes at least one of graphite, graphene, biochar, carbon spheres, carbon fiber, or carbon nanotubes. The amount of carbon-based material added is 0.5% to 5% of the mass of the catalyst powder.
4. The preparation method according to claim 1, wherein, The method for preparing the catalyst powder includes: Tin salt, antimony salt, and doped metal salt are added to an alcohol solvent to obtain a mixed solution; The mixture was reacted at 60~180℃ for 0.5~5h, and an alkaline substance was added during the reaction to obtain the precursor; The precursor is dried, ground, and then sintered at 500-800℃ for 2-5 hours to obtain the catalyst powder.
5. The preparation method according to claim 4, wherein, The alkaline substance is at least one of ammonia gas, ammonia water, or sodium hydroxide; When the alkaline substance is at least one of ammonia gas or ammonia water, the mixture is reacted at 60~180℃ for 0.5~5h, and an alkaline substance is added during the reaction to obtain a precursor comprising: The mixture is reacted at 60~180℃ for 0.5~5h, with ammonia gas or ammonia water continuously introduced during the reaction; the supernatant after the reaction is taken, ammonia water or sodium hydroxide is added, and then solid-liquid separation is performed to obtain the precursor; When the alkaline substance is sodium hydroxide, the mixture is reacted at 60~180℃ for 0.5~5h, and an alkaline substance is added during the reaction to obtain a precursor comprising: The mixture is reacted at 60~180℃ for 0.5~5h, and sodium hydroxide is added during the reaction; the precipitate after the reaction is taken to obtain the precursor.
6. The preparation method according to claim 1, wherein, The process of applying the mixed slurry to the surface of the titanium substrate and then performing heat treatment includes: The electrode is obtained by repeating the cycle of application, drying, application, drying and sintering 2 to 5 times, with the last sintering time being 1 to 2 hours. The application involves applying the mixed slurry onto the titanium substrate, the drying involves drying at 100-120°C for 10-20 minutes, and the sintering involves sintering at 500-700°C for 10-20 minutes.
7. An electrode, said electrode being prepared by the method according to any one of claims 1 to 6.
8. An electrochemical device comprising at least one electrode as claimed in claim 7.
9. The application of the electrode of claim 7 or the electrochemical device of claim 8 in the fields of wastewater treatment, drinking water purification, food processing, medical care, or fruit and vegetable preservation.
10. The application according to claim 9, wherein, The application is in electrochemical sterilization.
Citation Information
Patent Citations
Electrocatalyst, electrode coating and electrode for the preparation of chlorine
CN103981534A